2014
DOI: 10.1586/1744666x.2014.901889
|View full text |Cite
|
Sign up to set email alerts
|

Topical nasal lysine aspirin in aspirin-sensitive and aspirin-tolerant chronic rhinosinusitis with nasal polyposis

Abstract: Chronic rhinosinusitis patients with nasal polyps can be aspirin sensitive or aspirin tolerant. The majority belong to the latter group. They tolerate intake of aspirin or other non-steroidal anti-inflammatory drugs, whereas aspirin-sensitive patients have an adverse reaction (asthma, rhinitis and/or urticaria). Diagnosis of aspirin sensitivity is important for the patient, but is rarely undertaken in routine ENT or respiratory medicine practice. Treatment of nasal polyps is by a combination of medical therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Parikh et al have reported on the use of daily topical nasal lysine‐aspirin in aspirin‐sensitive patients. Interestingly, with only 75 mg applied intranasally, this study provided high level evidence for alterations of cysLT receptors and weaker evidence levels for improved clinical outcomes using this regimen 1671,1688 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 84%
“…Parikh et al have reported on the use of daily topical nasal lysine‐aspirin in aspirin‐sensitive patients. Interestingly, with only 75 mg applied intranasally, this study provided high level evidence for alterations of cysLT receptors and weaker evidence levels for improved clinical outcomes using this regimen 1671,1688 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 84%
“…Parikh and Scadding 1054,1063 have reported on the use of topical nasal lysine in aspirin-sensitive patients. Interestingly, with only 75 mg applied intranasally, they were able to provide level 1b evidence for alterations of cysLT receptors and weaker evidence levels for improved clinical outcomes using this regimen 1054,1063 (Table VIII-15).…”
Section: Viiie10 Crswnp and Aerd Managementmentioning
confidence: 99%
“…Parikh and Scadding 1054,1063 have reported on the use of topical nasal lysine in aspirin-sensitive patients. Interestingly, with only 75 mg applied intranasally, they were able to provide level 1b evidence for alterations of cysLT receptors and weaker evidence levels for improved clinical outcomes using this regimen 1054,1063 (Table VIII-15). In future trials, potential differences or clinical benefits of 100 mg vs 300 mg of aspirin or vice versa should be evaluated by randomized double-blind prospective dose-finding trials because the interpretation of the previously reported data in the literature are limited by their open study design.…”
Section: Viiie10 Crswnp and Aerd Managementmentioning
confidence: 99%
“…And, they are also centrally related to the pathogenesis of a large number of acute and chronic diseases, such as rheumatoid arthritis (Yang CLH et al 2013), colonic inflammatory response (Takhshid et al 2012) and periodontitis (Farhad et al 2013). However, the conventional therapies for inflammation, including steroids and nonsteroid anti-inflammatory drugs (NSAID) (Sostres et al 2010;Parikh & Scadding 2014;Carrasco-Pozo et al 2016), have shown many side effects and deficiencies. Considering this, licorice is an excellent alternative choice, due to the fact that it causes minimal disorders in the physiological functions of organism, has a nonspecific action and exerts a therapeutic action regardless of the direction of the pathological state.…”
Section: Introductionmentioning
confidence: 99%